Optimal Pore Chemistry in an Ultramicroporous Metal–Organic Framework for Benchmark Inverse CO2/C2H2 Separation. Issue 31 (29th June 2021) - Zhang, Zhaoqiang; Peh, Shing Bo; Krishna, Rajamani; Kang, Chengjun; Chai, Kungang; Wang, Yuxiang; Shi, Dongchen; Zhao, Dan
Abstract: Isolation of CO2 from acetylene (C2 H2 ) via CO2 ‐selective sorbents is an energy‐efficient technology for C2 H2 purification, but a strategic challenge due to their similar physicochemical properties. There is still no specific methodology for constructing sorbents that preferentially trap CO2 over C2 H2 . We report an effective strategy to construct optimal pore chemistry in a Ce IV ‐based ultramicroporous metal–organic framework Ce IV ‐MIL‐140‐4F, based on charge‐transfer effects, for efficient inverse CO2 /C2 H2 separation. The ligand‐to‐metal cluster charge transfer is facilitated by Ce IV with low‐lying unoccupied 4f orbitals and electron‐withdrawing F atoms functionalized tetrafluoroterephthalate, affording a perfect pore environment to match CO2 . The exceptional CO2 uptake (151.7 cm 3  cm −3 ) along with remarkable separation selectivities (above 40) set a new benchmark for inverse CO2 /C2 H2 separation, which is verified via simulated and experimental breakthrough experiments. The unique CO2 recognition mechanism is further unveiled by in situ powder X‐ray diffraction experiments, Fourier‐transform infrared spectroscopy measurements, and molecular calculations. Abstract : A charge‐ or electron‐transfer strategy within confined pore space is reported for the design of CO2 ‐selective ultramicroporous metal–organic frameworks with specific pore environments. Using this strategy, high CO2 capacities and high‐purity C2 H2 (> 99.9%) were obtained as proven by fixed bed breakthrough experiments.